PID - PROJETO DE INCLUSÃO DIGITAL- ENSINO MÉDIO E FUNDAMENTAL - ANO 6 - Padoin, Edson L.; Minelli, Leonardo; Pozzobon, Camila C.; Dill, Martin A.; Faccin, Fabio; Rohden, Rafael B.; Schuch, Regis R.; Sausen, Paulo S.; Dill, Sergio L. (Salão do Conhecimento, 2013)
Resumo